12(9-4r)=12(4+r)

Simple and best practice solution for 12(9-4r)=12(4+r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(9-4r)=12(4+r) equation:



12(9-4r)=12(4+r)
We move all terms to the left:
12(9-4r)-(12(4+r))=0
We add all the numbers together, and all the variables
12(-4r+9)-(12(r+4))=0
We multiply parentheses
-48r-(12(r+4))+108=0
We calculate terms in parentheses: -(12(r+4)), so:
12(r+4)
We multiply parentheses
12r+48
Back to the equation:
-(12r+48)
We get rid of parentheses
-48r-12r-48+108=0
We add all the numbers together, and all the variables
-60r+60=0
We move all terms containing r to the left, all other terms to the right
-60r=-60
r=-60/-60
r=1

See similar equations:

| 9x-0.75=0.416 | | 7+5x-8x=16 | | -7(-7-2b)=119 | | -18=-18v | | –6x+4=–8x–12 | | 2x+-31=2x−31 | | -8+|-8b+8|=72 | | 12x-6=3(4x+9) | | 1^4x+5=18 | | 12x-6=3(4x-9) | | 5x-15=7-4x | | 2+7x=20-3x | | 7x^2-30=0 | | 9e+4=-5+15+13e | | -20+7-8z=-7z+7 | | -6(8-x)=7(x-4)-5 | | -(5+8)+n=-(8n-7) | | 15-(x+5)=7x-6 | | 4-7(-4p+7)=-129 | | 2x+5x-5=44 | | 5(-9+x)=-15 | | -6(8-x=7(x-4)-5 | | 22=(3.14)r | | z/7+42=56 | | 8.3g-14.81=17.5+8.61+11.4g | | 7k-3-8k=-5 | | 3/4h-1/3h+11=8 | | 237=62-x | | 18-3p=-4p | | -4(r-7)+5=-9-6(r-10) | | 67-w=179 | | x+109=x=89 |

Equations solver categories